Efektivitas Posisi Semi Fowler 45° pada Kualitas Tidur Pasien Congestive Heart Failure - Nourma Nurlita Sari, Nourma; Rahmasari, Ikrima; Widiastuti, Agung; Utomo, Endrat Kartiko; Yudhianto, Kresna Agung (Universitas Muhammadiyah Klaten, 2025)
Sleep disturbance is a common problem in patients with Congestive Heart Failure (CHF), often caused by disease symptoms such as dyspnea, which negatively impacts their quality of life. The 45° Semi-Fowler's position is a simple non-pharmacological nursing intervention that can improve lung expansion, reduce cardiac workload, and enhance patient comfort, thereby potentially improving sleep quality.This study aimed to determine the effect of the 45° Semi-Fowler's position on the sleep quality of CHF patients at RSUD dr. Moewardi Surakarta. This research employed a quasi-experimental design with a one-group pretest-posttest approach. A total of 32 CHF patients were selected using a purposive sampling technique.The intervention, applying the 45° Semi-Fowler's position, was administered for 30 minutes daily over three consecutive days. Prior to the intervention, patients were generally positioned supine or with minimal elevation. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), and data were analyzed with the Wilcoxon Signed-Rank Test.The results showed a statistically significant difference in PSQI scores before and after the intervention (p < 0.05), with the median score decreasing from 7.00 (Poor Quality) to 4.00 (Good Quality)10. This clinically significant reduction suggests a positive impact of the positioning.This study concludes that the 45° Semi-Fowler's position is effective in improving the sleep quality of CHF patients and can be recommended as a standard nursing intervention, though future studies should utilize a Randomized Controlled Trial design to control for confounding factors, such as the placebo effect